Assessment of miR-182, miR-221 and CEA Expression in the Peripheral Blood of Oral Squamous Cell Carcinoma (OSCC) Patients - Rasouli, Amir; Arzi, Laleh; Khademi, Saideh; Mohamadnia, Abdolreza (Journal of craniomaxillofacial research (Online), 2023)
Introduction: Head and neck cancer is the sixth common cancer in the world, of which the oral cavity is the most frequent type. It was diagnosed on more than 377,700 cases worldwide in 2020. Access to high-quality care leading to a more specific and earlier diagnosis of this cancer is crucial. Therefore, researchers attempt to investigate and detect efficient biological tumor marker. The present study aimed to investigate the changes in the expressions of miR-182, miR-221, and carcinoembryonic antigen (CEA) in the peripheral blood of patients with oral squamous cell carcinoma (OSCC) and compare them with healthy individuals to detect early OSCC. Materials and Methods:30 peripheral blood samples from patients with OSCC (19 male and 11 female), aged 25-70, were obtained from the cancer institute of Tehran University of Medical Sciences, and 30 peripheral blood samples from healthy individuals (20 male and 10 female) aged 26-70 were collected. Real-time PCR was carried out to investigate the differences in the expressions of miR-182, miR-221, and ELISA was used to measure CEA protein expression. Results: Among the subjects with OSCC 83% showed miR-182 expression, 93% revealed miR-221 expression and 96% demonstrated CEA expression. Whereas, these expressions were 26%, 20% and 13%, respectively, for the healthy group. The simultaneous detection of miR-182 and miR-221 was 73% in the individuals with OSCC. The simultaneous observation of miR-182, miR-221, and CEA in the group with OSCC was 60%. The expression level of miR-221 in the group with OSCC was 2.63 times that of the healthy subjects, and the expression level of miR-182 in the individuals with OSCC was 2.29 times that of the healthy group. Conclusion: The results of this study nominated miR-182, miR-221, and CEA as biomarkers for early diagnosis and consequently improvement of survival rate of patients suffering from OSCC.